Welcoming, supportive care in US birthing facilities and realization of breastfeeding goals. (August 2022) - Pearsall, Marina Stranieri; Stuebe, Alison M.; Seashore, Carl; Sullivan, Catherine; Tully, Kristin P.
Abstract: Background: Emotional and physical support for birthing parents is positively associated with realization of their breastfeeding goals. However, few studies have investigated maternal descriptions of their postnatal unit experience of these domains. Research Aim: The objective was to investigate maternal report of their birthing facility experiences and quantify the extent to which accounts of postpartum support were associated with meeting their breastfeeding goals. Methods: After IRB review, data were obtained through an online survey distributed from November 2016-May 2017. This analysis utilizes data from 2, 771 birthing parents who were at least 18 years of age, experienced maternity care in the United States within five years, and reported that they had intended to breastfeed. Bivariate analysis was followed by logistic regression controlling for significant covariates. Results: In this sample of primarily non-Hispanic white birthing parents with intent to exclusively breastfeed, the following postnatal unit variables were associated with higher odds of meeting their breastfeeding goals, birthing parents feeling: welcomed (adjusted OR=1.36), that health care promoted their physical health (adjusted OR=1.41), that care promoted their emotional health (adjusted OR=1.38), that they were supported (adjusted OR=1.56), and that they were recognized by their health care team (adjusted OR=1.30). All the measured postnatal unit support variables were significantly correlated with each other, with correlation coefficients ranging from 0.15 to 0.81. Conclusions: Before the COVID-19 pandemic, birthing parents' experiences on the postnatal unit were interrelated and associated with meeting their breastfeeding goals. As health care services are reviewed and prioritized during the COVID-19 pandemic and as part of ongoing strengthening of systems, qualitative and observational research can address the mechanisms underlying breastfeeding outcomes to inform the provision of more holistic and effective support.